Solar photovoltaic systems in Bangladesh : experiences and opportunities - International Workshop on "Dissemination of Solar Photovoltaic Energy" (1999 : Dhaka, Bangladesh); Eusuf, M.; Bangladesh Centre for Advanced Studies (Dhaka : The University Press, 2005)
Contributed articles presented at International Workshop on "Dissemination of Solar Photovoltaic Energy" held on 28-29 May, 1999 at Dhaka, Bangladesh.
"Bangladesh Centre for Advanced Studies."
Includes bibliographical references and index.
Keywords: Photovoltaic power systems -- Bangladesh -- Congresses